Extracellular Vesicles in the Development of the Non-Alcoholic Fatty Liver Disease: An Update - Vicneswarry Dorairaj; Siti Aishah Sulaiman; Nadiah Abu; Nor Azian Abdul Murad (Biomolecules, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a broad spectrum of liver damage disease from a simple fatty liver (steatosis) to more severe liver conditions such as non-alcoholic steatohepatitis (NASH), fibrosis, and cirrhosis. Extracellular vesicles (EVs) are a heterogeneous group of small membrane vesicles released by various cells in normal or diseased conditions. The EVs carry bioactive components in their cargos and can mediate the metabolic changes in recipient cells. In the context of NAFLD, EVs derived from adipocytes are implicated in the development of whole-body insulin resistance (IR), the hepatic IR, and fatty liver (steatosis). Excessive fatty acid accumulation is toxic to the hepatocytes, and this lipotoxicity can induce the release of EVs (hepatocyte-EVs), which can mediate the progression of fibrosis via the activation of nearby macrophages and hepatic stellate cells (HSCs). In this review, we summarized the recent findings of adipocyte- and hepatocyte-EVs on NAFLD disease development and progression. We also discussed previous studies on mesenchymal stem cell (MSC) EVs that have garnered attention due to their effects on preventing liver fibrosis and increasing liver regeneration and proliferation.